High-Definition Transcranial Direct Current Stimulation Over the Right Lateral Prefrontal Cortex Increases Maximization Tendencies - Wang, Haixia; Zhang, Hanqi (Frontiers in Behavioral Neuroscience, 2021)
Getting the best affects every aspect of life. Despite its importance, remarkably little is known about the neurobiological mechanisms supporting the process of getting the best, i.e., maximization. Our study demonstrates that maximization tendency can be increased with high definition transcranial direct-current stimulation (HD-tDCS) over the right dorsolateral prefrontal cortex (DLPFC). Participants (n=64) received 2 mA anodal 4×1 HD-tDCS or sham stimulation over the right DLPFC in two sessions, and subsequently completed N-back working memory task and Maximization Scale. We found that maximization tendency scores increased through anodal stimulation. Furthermore, our study found that this increase in maximization tendency might be driven by the change on motivation (the alternative search subscale of maximization scale was measurably increased, which demonstrated that the enhancement of motivation to search more option for the best), instead of the change on working memory. These results demonstrated that maximization tendency can be strengthened by noninvasive interventions and right DLPFC has causal relationship with maximization tendency.